Sustainable leadership : lessons of vision, courage, and grit from the CEOs who dared to build a better world - Murphy, Clarke (John Wiley & Sons, Inc., 2022)
"CEOs are now expected to deliver results that both increase the bottom line and drives value for all stakeholders, not just shareholders. But they aren't equipped with the understandings necessary to remake their organization and business model for sustainable business goals. Sustainable Leadership provides that education. It's the toolkit for leaders in the age of stakeholder capitalism, who are tasked with producing extraordinary profits while also delivering on green business and workforce development goals. Offering a step-by-step framework on how to develop your sustainable leadership muscles--and identify and nurture these skills in your next-gen leaders--Sustainable Leadership will help readers set a vision for change, make bold decisions, and debunk the myth that sustainability is at odds with profitability. It is a timely guide for bold leaders aspiring to make a greater impact and help build a better, more resilient future--and achieving business growth simultaneously"--